Language Change in Social Media (Instagram) - Muhammad Natsir; Bahagia Saragih; Puan Suri Mira A.; Rafika Dewi; Lidiman Sahat Martua Sinaga (Randwick International of Social Science Journal, 2020)
This research was aimed to analyze the language change in Indonesian language. The analysis was focused on the Indonesian adjectives change found in social media (Instagram). This research was conducted by using qualitative method. The data of this study were the most common thirty adjectives found in social media especially Instagram. as the data source because most of young generations nowadays tend to use Instagram as a mean of communication. The researcher observed and chose the most common thirty adjectives found on Instagram by using an observation list. There were some techniques of data analysis performed, namely: determining, observing, choosing, translating, analyzing, and drawing conclusion. Based on the data analysis conducted, it was found that all the adjectives are changing into special terms which are totally different form the original words. Furthermore, language change is caused by the globalization and the interaction of people. It was also found that some of the words are changing into English. Abbreviation and contractions also occur in the process of language change.